Modulation of Immune Cell Functions by the E3 Ligase Cbl-b - Lutz-Nicoladoni, Christina; Wolf, Dominik; Sopper, Sieghart (Frontiers in Oncology, 2015)
Maintenance of immunological tolerance is a critical hallmark of the immune system. Several signaling checkpoints necessary to balance activating and inhibitory input to immune cells have been described so far, among which the E3 ligase Cbl-b appears to be a central player. Cbl-b is expressed in all leukocyte subsets and regulates several signaling pathways in T cells, NK cells, B cells and different types of myeloid cells. In most cases Cbl-b negatively regulates activation signals through antigen or pattern recognition receptors and co-stimulatory molecules. In line with this function, cblb-deficient immune cells display lower activation thresholds and cblb knockout mice spontaneously develop autoimmunity and are highly susceptible to experimental autoimmunity. Interestingly, genetic association studies link cblb-polymorphisms with autoimmunity also in humans. Vice versa, the increased activation potential of cblb-deficient cells renders them more potent to fight against malignancies or infections. Accordingly, several reports have shown that cblb knockout mice reject tumors, which mainly depends on cytotoxic T and NK cells. Thus targeting Cbl-b may be an interesting strategy to enhance anti-cancer immunity. In this review we summarize the findings on the molecular function of Cbl-b in different cell types and illustrate the potential of Cbl-b as target for immunomodulatory therapies.